Industri dan Dinamika Masyarakat: Studi Kasus di Kecamatan Citangkul Kota Cilegon - -, Syaifullah (Jurnal Civicus, 2008)
Industri dan Dinamika Masyarakat: Studi Kasus di Kecamatan Citangkul Kota Cilegon